2018
DOI: 10.1080/07420528.2018.1430036
|View full text |Cite
|
Sign up to set email alerts
|

Decreased daytime light intensity at nonwindow hospital beds: Comparisons with light intensity at window hospital beds and light exposure in nonhospitalized elderly individuals

Abstract: Light is crucial for the synchronization of internal biological rhythms with environmental rhythms. Hospitalization causes a range of unfavorable medical conditions, including delirium, sleep disturbances, depressed mood, and increased fall, especially in elderly people. The hospital room environment contributes significantly to patients' circadian physiology and behavior; however, few studies have evaluated light intensity in hospital settings. In this study, bedside light intensity during the daytime (6:00-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Light exposure is known to suppress blood and saliva levels of melatonin via the retinohypothalamic pathway and suprachiasmatic nucleus ( Sadun et al, 1984 ). Bright (>2500 lux) light was found to suppress melatonin levels completely ( Arendt, 2005 ) but even overhead lighting of much lower brightness (100 lux from fluorescent bulbs) can cause significant suppression ( Bojkowski et al, 1987 ; Harada, 2004 ; Iwamoto et al, 2018 ). Initially, it was believed melatonin levels decrease linearly in proportion to the light exposure from 700 Lux ( Mayeda et al, 1998 ).…”
Section: Protocol Considerationsmentioning
confidence: 99%
“…Light exposure is known to suppress blood and saliva levels of melatonin via the retinohypothalamic pathway and suprachiasmatic nucleus ( Sadun et al, 1984 ). Bright (>2500 lux) light was found to suppress melatonin levels completely ( Arendt, 2005 ) but even overhead lighting of much lower brightness (100 lux from fluorescent bulbs) can cause significant suppression ( Bojkowski et al, 1987 ; Harada, 2004 ; Iwamoto et al, 2018 ). Initially, it was believed melatonin levels decrease linearly in proportion to the light exposure from 700 Lux ( Mayeda et al, 1998 ).…”
Section: Protocol Considerationsmentioning
confidence: 99%
“…Several studies have reported the effects of low levels of light exposure in patients in windowless hospital beds. For example, daylight hours have been reported to be reduced in windowless hospital beds [2]. Furthermore, patients staying in windowless rooms in the intensive care unit have been reported to be more prone to delirium than those in rooms with windows [3].…”
Section: Introductionmentioning
confidence: 99%